The VPAC1 receptor: structure and function of a class B GPCR prototype - Couvineau, Alain; Ceraudo, Emilie; Tan, Yossan Var; Nicole, Pascal; Laburthe, Marc (Frontiers in Endocrinology, 2012)
The class B G protein-coupled receptors (GPCRs) represents a small sub-family encompassing 15 members, and are very promising targets for the development of drugs to treat many diseases such as chronic inflammation, neurodegeneration, diabetes, stress and osteoporosis. The VPAC1 receptor which is an archetype of the class B GPCRs binds Vasoactive Intestinal Peptide (VIP), a neuropeptide widely distributed in central and peripheral nervous system modulating many physiological processes including regulation of exocrine secretions, hormone release, foetal development, immune response... VIP appears to exert beneficial effect in neuro-degenerative and inflammatory diseases. This article reviews the current knowledge regarding the structure and molecular pharmacology of VPAC1 receptors. Over the past decade, structure-function relationship studies have demonstrated that the N-terminal ectodomain (N-ted) of VPAC1 plays a pivotal role in VIP recognition. The use of different approaches such as directed mutagenesis, photoaffinity labeling, Nuclear Magnetic Resonance (NMR), molecular modeling and molecular dynamic simulation has led to demonstrate that: i) the central and C-terminal part of the VIP molecule interacts with the N-ted of VPAC1 receptor which is itself structured as a « Sushi » domain; ii) the N-terminal end of the VIP molecule interacts with the first transmembrane domain of the receptor where three residues (K143, T144 and T147) play an important role in VPAC1 interaction with the first histidine residue of VIP.